2022
DOI: 10.1002/iid3.619
|View full text |Cite
|
Sign up to set email alerts
|

Retinal microvascular impairment in COVID‐19 patients: A meta‐analysis

Abstract: Background The coronavirus disease 2019 (COVID‐19), caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), has led to a global pandemic in an unprecedented time frame. Systemic vascular involvement in COVID‐19 has been identified, and SARS‐CoV‐2 has also been found to cause multiple organ ischemia and posterior ocular segment disease in mammals, raising concerns about the human retinal microvascular involvement in SARS‐CoV‐2. Objective To objectively as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…While there is no robust evidence for a direct infection of endothelial cells by SARS-CoV-2 [94][95][96] , multiple studies suggest capillary damage in various organs 97 and functional impairment of the microvasculature has been implicated in the pathogenesis of COVID-19 acutely in the pandemic [98][99][100][101][102] . We didn't find overt signs of neurovascular damage, increased thrombosis, endothelial destruction or bleedings in our brainstem samples.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no robust evidence for a direct infection of endothelial cells by SARS-CoV-2 [94][95][96] , multiple studies suggest capillary damage in various organs 97 and functional impairment of the microvasculature has been implicated in the pathogenesis of COVID-19 acutely in the pandemic [98][99][100][101][102] . We didn't find overt signs of neurovascular damage, increased thrombosis, endothelial destruction or bleedings in our brainstem samples.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Several studies on the microvascular manifestations in the retina secondary to SARS-CoV-2 infection have recently been published, showing that mean macular capillary vessel density was significantly lower and with low levels of peripapillary perfusion density in patients with COVID-19 compared to age-matched normal controls, but without evidence of infection. 7 , 8 On the other hand, the scientific literature has reported central nervous system (CNS) involvement by COVID-19 infection and the neurotropic potential of SARS-CoV-2. 9 The neurological symptoms and complications in COVID-19, however, are few and inconclusive, and no long-term follow-up has been performed to date, and it has been reported that it can cause optic nerve edema.…”
Section: Introductionmentioning
confidence: 99%